Study on distance measurement words in the English and Uzbek languages - Shamuratova, Muborak (The Lingua Spectrum, 2025)
The article provides an overview of the words expressing units of measurement in English and Uzbek. A comparative study of these two languages is considered relevant. Firstly, the research describes spatial and distance-related metalexemes in both languages. Then, by using thesauri, thematic dictionaries, and corpora, qualitative approaches are applied to determine and evaluate the quantity, pragmatics, and communicativity of the word-measure expressions, along with the context of their pronunciation. The study then outlines several categories, analyzing measurement words from both languages in terms of their etymology, classifying them as traditional units, SI units, and foreign units, and examining their usage in different contexts. The article highlights both the differences and similarities. A detailed analysis of the contexts allows for conclusions about word combinations. Furthermore, the study considers the influence of these expressions and emphasizes that understanding the historical and political background of English and Uzbek can help overcome translation issues in the field of translation studies. Based on the examined data, the research shows that all types of measurement words are used in both English and Uzbek. However, their frequency of use, contexts, and speech situations differ. Some categories are typically used within a limited range of topics, while others are not restricted in their usage. This research is expected to contribute to practical applications.